The effect of Cornus mas extract on nıcotıne-ınduced oxıdatıve stress and ıntratestıcular damage ın male rats: Nicotine damage and Cornus mas effect - Öztekin, Ünal; Caniklioğlu, Mehmet; Ateş, Şükrü; Doğanyiğit, Züleyha; Kaymak, Emin; Fırat, Fatih; Göçmen, Ayşe Yeşim; Ataç, Fatih; Attar, Rukset; Yılmaz, Seher (Cellular and Molecular Biology, 2023)
The role of oxidative stress in disease pathogenesis has been extensively investigated. Researchers have gathered sufficient evidence related to oxidative stress-mediated intratesticular damage. The aim of this was study to evaluate the effects of Cornus Mas (CM) extract on intratesticular changes in rats exposed to nicotine. Thirty Wistar albino rats were divided into four groups. The groups and the administrated agents for 35 days were as follows; Control group (n=6): 0.9% saline, intraperitoneally; Nicotine group (n=7): 4 mg/kg nicotine, subcutaneous; CM group (n=7): 1000 mg/kg CM extract in 0.5 ml saline, via gavage; Nicotine + CM Group (n=8): 4 mg/kg Nicotine, subcutaneous + 1000 mg/kg CM extract via gavage. One rat each from the groups Nicotine and CM died. In spermatogenetic and histopathological examination, significant positive changes were detected in nicotine + CM group regarding seminal parameters, apoptotic cells, Factor VIII and Johnsen score as compared to nicotine group. Oxidative stress markers were higher in nicotine group as compared to the control group. OSI and MDA levels were found to be reduced in nicotine + CM group than nicotine group. Nicotine induced a significant increase in TNF-α and IL-6 levels compared to the control group; however, CM effectively counteracted this increase. We have shown that nicotine increases testicular damage, causes apoptosis of testicular cells and adversely affects spermatogenesis by increasing inflammation. We concluded that CM extract exerted beneficial effects on spermatogenesis and minimized testicular parenchymal damage, apoptosis and angiogenesis. Rapidly increasing understanding of the complexity of oxidative stress in intratesticular is the key to unlocking the potential of ROS-targeting therapies.